2012
DOI: 10.3233/bir-2012-0619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term feeding of α-glucosylhesperidin on the mechanical properties of rabbit femoral arteries

Abstract: Many people are sensitive to cold, resulting in poor blood circulation. There is evidence that hesperidin results in increased peripheral circulation and skin temperature. A transglycosylated hesperidin, α-glucosylhesperidin, is more bioabsorbable than hesperidin. In the present study, biomechanical studies were performed on the effects of long-term feeding of α-glucosylhesperidin on the contractile response (diameter response) and stiffness of femoral arteries excised from rabbits. Animals in the normal (non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…5), and lycium or LLA led to the faster recovery of the skin surface temperature, thus it is expected to protect the body from heat loss. Hesperidin composed in lycium fruits and LLA, which can increase peripheral circulation and skin temperature under coldness [24,25], thus supports the present study. Furthermore, the polysaccharides of lycium fruits shown antihypertensive effect by a significant decrease in the concentration of phenylephrine in isolated aortic rings [22], and improved the thoracic aorta vasoreactivity in rats under exhaustive exercise [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5), and lycium or LLA led to the faster recovery of the skin surface temperature, thus it is expected to protect the body from heat loss. Hesperidin composed in lycium fruits and LLA, which can increase peripheral circulation and skin temperature under coldness [24,25], thus supports the present study. Furthermore, the polysaccharides of lycium fruits shown antihypertensive effect by a significant decrease in the concentration of phenylephrine in isolated aortic rings [22], and improved the thoracic aorta vasoreactivity in rats under exhaustive exercise [27].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been reported that polysaccharides the increase of blood pressure in hypertension rats, and the arterial compliance by up-regulation of the eNOS expression and improvement of the endothelium the rat aorta ring [22,23]. In addition, hesperidin, a flavonoid composed in lycium fruits [9], resulted in increased peripheral circulation and skin temperature under cold intolerance and rat models [24,25]. On the other hand,…”
Section: Introductionmentioning
confidence: 99%